The Influence of Financial Knowledge and Financial Attitude on Investment Decisions of UIN Raden Mas Said Surakarta Students - Assyarofi, Muhammad Rexsa; Muntafiah; Ulin Nisa; Endang Rahmawati; Septian Agung Wijayanto (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This study aims to analyze the effect of financial knowledge, and financial attitude on investment decision. The sample of this research is Students at the State Islamic University Raden Mas Said Surakarta. Samples were selected using a non-probability sampling method totaling 200 respondents by distributing questionnaires online using Google Forms. The analysis technique used is multiple linear regression supported by the SPSS program version 22.0. the results obtained in this study are that there is a positive influence on financial knowledge, and financial attitude on investation decisions in Student at the State Islamic University Raden Mas Said Surakarta